Uptake and Tolerance of Chemotherapy in Elderly Patients with Small Cell Lung Cancer and Impact on Survival. (29th November 2012) - Fisher, Stacey; Al-Fayea, Turki M.; Winget, Marcy; Gao, He; Butts, Charles
Abstract : The treatment of elderly cancer patients is complicated by many factors. We sought to assess the uptake and tolerance of chemotherapy among patients 75 years and older diagnosed with small cell lung cancer (SCLC) in years 2004–2008 in Alberta, Canada, and assess their survival. All patients who met the above criteria and had an oncologist-consult were included. Data were obtained from the Alberta Cancer Registry and chart review. A total of 171 patients were included in the study, 117 (68%) of whom began chemotherapy. Of those, 52% completed all cycles, 66% did not have any dose reductions, and 31% completed all cycles at the recommended dose. The risk of death for patients who did not complete all cycles of chemotherapy was 2.72 (95% CI: 1.52–4.87) and for those who completed all cycles but with a reduced dose was 1.02 (95% CI: 0.57–1.82) relative to those who completed chemotherapy at full dose after adjusting for several demographic/clinical factors. Our results suggest that a significant proportion of elderly patients are able to tolerate chemotherapy and receive a survival benefit from it while those who experience toxicity may receive a survival benefit from a reduction in chemotherapy dose as opposed to stopping treatment.